Lipid profile of childhood cancer survivors and the effects of vitamin D supplementation: a prospective study - Shaimaa Kandil; Ashraf Fouda; Khadijah Boujettif; Yasmin Salama; Suzy Abdelmabood (SpringerOpen, 2021)
Abstract Background Childhood cancer survivors (CCS) have high prevalence of obesity vitamin D (VD) deficiency together with dyslipidemia. We aimed to evaluate lipid profile and the effect of VD supplementation in CCS. Results VD deficiency was more frequent among obese CCS and their lipid profiles, TC, and LDL-C levels were significantly higher compared to non-obese patients. After VD supplementation trials, VD levels increased among obese and non-obese children albeit it was significantly higher in non-obese subjects while the lipid profile of obese patients significantly decreased. Also, parathyroid hormone levels were persistently elevated among VD-deficient obese patients. Yet, the weight of obese patients remained unchanged. Conclusion VD deficiency was more prevalent among obese CCS. VD supplementation helped in normalization of the lipid profile of obese CCS. Regular measurement of PTH and 25OH-VD is recommended for CCS especially obese ones who may need VD supplementation.